On q-SZASZ- Mirakyan Operators of functions of Two Variables - Mohammad, Ali; Kadum, Rafah (Iraqi Journal of Science, 2024)
In this paper, we define two operators of summation and summation-integral of q-type in two dimensional spaces. Firstly, we study the convergence of these operators and then we prove Voronovskaya- type asymptotic formulas for these operators.